PILOTING A MODEL OF EDUCATIVE AND ATTRACTIVE PHYSICAL ACTIVITIES BASED ON DOLANAN ANAK - Wawan Sundawan Suherman; Soni Nopembri; Nur Rohmah Muktiani (Jurnal Kependidikan, 2015)
This study was aimed at applying Majeda based on Dolanan Anak as a means of optimizingkindergarteners’ growth and development. This study was conducted in small- and large-scaletryouts. The study employed the research and development approach. The small-scale piloting wasconducted at TK/SD Model Sleman and TK PKK Temanggal, Sleman while the large-scale tryoutwas conducted at TKN Pembina Wonosari, TK ABA Kauman Yogyakarta, TKN Pembina Galur,TKN 1 Sleman, and TK ABA Karangmojo XVII. The results show that the model format needs tobe revised into new Majeda that consist of six components. The guideline needs to be revised intofour sections. Based on the results of the piloting, it can be concluded that Majeda based on DolananAnak is appropriate for further operational testing